Health Financing and Delivery in Vietnam : Looking Forward - Lieberman, Samuel S. (World Bank, 2012)
This book reviews Vietnam's successes and the challenges it faces, and goes on to suggest some options for further reforming the country's health system. Options for expanding coverage to 100 percent of the population are compared. The issue of how to deepen coverage, so that insurance reduces out-of-pocket spending by more than it does at present, is also discussed, as is the issue of how to put downward pressure on the cost of health care. The book also looks at the issues of how to improve the quality of care, both overall and at the hospital level, and how to reform provider payment methods. It also looks at the issue of stewardship, what different parts of government (the health ministry, the health insurer, and so on) should be doing at each level of government, and what different levels of government (the central government, provincial government, and so forth) ought to be doing.